Sosialisasi Pendidikan Anti Korupsi bagi Siswa Sekolah Menengah di Kota Metro, Lampung: Upaya Menanamkan Nilai Integritas Sejak Dini - Anugrah Putra Kusuma Anugrah; Shely Nasya Putri; Nyimas Lidya Putri Pertiwi; Nency Dela Oktora; Achsani Taqwim Jindan Al-Ustadzi; Nabila Alfiyatussofa (Swadaya: Jurnal Pengabdian Masyarakat, 2026)
The importance of instilling anti-corruption principles early on, especially in secondary schools, underlies this community service activity. Corruption is a serious problem that affects the nation's social, economic and moral order. Therefore, anti-corruption education must be provided to the younger generation as a preventive effort in building a moral character. The purpose of this activity is to improve students' understanding of the concept of corruption, the negative impacts it causes, the different types and forms of punishment, and the factors that cause corruption to emerge in Indonesia. The activity was conducted at TMI Roudlatul Qur'an High School in Metro City, Lampung, especially in class XI.1, with classical learning method. As teaching materials, the Materials were delivered through PowerPoint presentations on the blackboard and explained interactively by the service team in class. This community service activity has achieved its main objective, which is to increase students' understanding and awareness of anti-corruption concepts, impacts, and values, which can be achieved through the educational-participatory approach used. This is demonstrated by the improvement in students' understanding of the definition of corruption, types of corruption, and its negative impacts on social and national life, as seen from students' responses during discussion sessions, Q&A, and educational games. Although students were initially passive at the beginning of the activity, their involvement increased with the use of interactive methods relevant to the characteristics of secondary school students